2008
DOI: 10.1111/j.1601-0825.2007.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretching force‐induced early apoptosis in human periodontal ligament cells

Abstract: The overall results suggested that stretching force not only influenced morphology but also induced early apoptosis in human PDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
4
31
1
Order By: Relevance
“…The fraction of apoptotic hPDL cells was significantly upregulated, in comparison to the control, following exposure to 6 or 24 h. Figure. 4b showed that the rate of apoptosis reached a peak when the cells were compressed for 24 h. These results are supported by those previously reported in other models namely the stretching force model in hPDL cells 32) and the compression force model in osteoblast 33) . Furthermore, after staining with Hoechst 33258, the PDL cells which were subjected to a compression force exhibited the typical morphological features of apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The fraction of apoptotic hPDL cells was significantly upregulated, in comparison to the control, following exposure to 6 or 24 h. Figure. 4b showed that the rate of apoptosis reached a peak when the cells were compressed for 24 h. These results are supported by those previously reported in other models namely the stretching force model in hPDL cells 32) and the compression force model in osteoblast 33) . Furthermore, after staining with Hoechst 33258, the PDL cells which were subjected to a compression force exhibited the typical morphological features of apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Caspase-3 is considered to be a central mediator of apoptosis and is one of the major activated cysteine proteases in the caspase family that is pivotal in apoptosis[41]. It was reported that cyclic stretch-induced apoptosis was controlled by caspase-3[42]. Considering its importance in apoptosis, we observed cleaved caspase-3 protein levels in the current study, indicating an association with increased apoptosis in osteoblasts responding to large-magnitude mechanical stress.…”
Section: Discussionsupporting
confidence: 64%
“…Cells reached confluence following 3 d of culture and then were subjected to cyclic stretch using a Flexcell Tension Plus system (FX-5000T, Flexcell International) with a 20% elongation magnitude for 6 or 24 h. Cells cultured on the same kind of plates but without stretch loading were used as time-matched control cells. The loading frequency of 6 cycles/min (5 s stretch and 5 s relaxation) was the same to that in our previous studies [17, 18]. Three independent loading experiments were carried out in every group.…”
Section: Methodsmentioning
confidence: 99%